Freezing propagation of condensate droplets at early stage of frosting on vertical hydrophobic surface. (January 2023) - Wang, Feng; Dai, Fei; Liang, Caihua; Zhang, Xiaosong
Abstract: As condensate droplets formed at the early stage of frosting are the foundation of frost layer growth, to study the freezing propagation of condensate droplets is of great significance to understand the frosting process. In this paper, the influencing factors of lateral spreading of frost crystals and freezing propagation modes of condensation droplets were discussed by visualization experiments, and the propagation mechanism was revealed combined with theoretical analysis. It is observed that condensate droplets relies on the lateral spreading of frost crystals to realize the freezing propagation and frost crystals diffuse to the center of the cold surface with the help of freezing droplets. The lateral spreading of frost crystals is the key to achieve freezing propagation of condensate droplets, which is accompanied by the evaporation of droplets with small size. The freezing propagation of condensate droplets is affected by the lateral spreading rate of frost crystals and the droplet spacing. Increasing the contact angle of the cold surface reduces the freezing propagation rate and delay frost formation. Interestingly, two freezing propagation modes, "contact-freeze" and "absorption-freeze", are observed when the frost crystals contact the subcooled droplets. Increasing the surface contact angle or reducing the contact angle hysteresis can increase the frequency of the "absorption-freeze" mode, which helps to reduce the freezing propagation rate of condensate droplets.